New dual-stage pH control fed-batch cultivation strategy for the improvement of lipids and carotenoids production by the red yeast Rhodosporidium toruloides NCYC 921. (August 2015) - Dias, Carla; Sousa, Sofia; Caldeira, João; Reis, Alberto; Lopes da Silva, Teresa
Highlights: Medium pH for the lipid and carotenoid production by R. toruloides is different. A dual step pH control fed-batch strategy improved the yeast products production. The oxygen played a crucial rule in the yeast carotenoid synthesis. Abstract: The optimal medium pH to produce biomass and fatty acids by the red yeast Rhodosporidium toruloides NCYC 921 is 4.0, and to produce carotenoids is 5.0. Based on this difference, a dual-stage pH control fed-batch cultivation strategy for the enhancement of lipids and carotenoids production by this yeast was studied. The results showed that when the yeast growth phase was conducted at pH 4.0, and the products accumulation phase was conducted at pH 5.0, biomass, total fatty acid and total carotenoid productivities were significantly improved comparing with the yeast fed batch cultivations carried out at fixed medium pH (4 or 5). Under dual-stage pH control conditions, the biomass, carotenoids and lipids productivities attained 2.35 g/L h, 0.29 g/L h and 0.40 g/L h, respectively. It was also observed that the oxygen played a major role in the yeast carotenoid production.